A novel electro-hydraulic compound braking system coordinated control strategy for a four-wheel-drive pure electric vehicle driven by dual motors. (15th February 2022) - Tang, Qingsong; Yang, Yang; Luo, Chang; Yang, Zhong; Fu, Chunyun
Abstract: The electro-hydraulic compound braking system of a pure electric vehicle can recover the energy released during braking and store it in the battery through the motor, thereby improving the vehicle's energy utilization efficiency. However, how to coordinate the control of motor braking and hydraulic braking during vehicle braking to ensure the optimal balance of vehicle braking safety and energy recovery efficiency is still an urgent problem to be solved in the field of new energy vehicles. This paper takes the four-wheel-drive pure electric vehicle driven by dual motors as the research object and proposes a coordinated control strategy for an electro-hydraulic hybrid brake system with efficient energy recovery. The proposed coordinated control strategy is composed of two parts: the braking force distribution control strategy that comprehensively considers braking safety and charging efficiency optimization and the coordinated control strategy of regenerative braking system (RBS) and anti-lock braking system (ABS) based on model predictive control. The results show that the proposed coordinated control strategy has superior braking performance, and improves the energy recovery efficiency by more than 22.76% compared with the conventional coordinated control strategy, proving the effectiveness of efficient energy recovery under the premise of ensuring stability and safety. Highlights: The accurate model of the electric vehicle driven by dual motors is established. The optimization of the charging efficiency for the braking system is studied. The proposed control strategy has a high utilization of the road adhesion coefficient. The braking energy recovery efficiency can be improved by more than 22.76%.